Building partnerships for healthy environments: research, leadership and education. (1st December 2014) - Thompson, Susan; Kent, Jennifer; Lyons, Claudine
Abstract : As populations across the globe face an increasing health burden from rising rates of obesity, diabetes and other lifestyle‐related diseases, health professionals are collaborating with urban planners to influence city design that supports healthy ways of living. This paper details the establishment and operation of an innovative, interdisciplinary collaboration that brings together urban planning and health. Situated in a built environment faculty at one of Australia's most prestigious universities, the Healthy Built Environments Program (HBEP) partners planning academics, a health non‐government organisation, local councils and private planning consultants in a state government health department funded consortium. The HBEP focuses on three strategic areas: research, workforce development and education, and leadership and advocacy. Interdisciplinary research includes a comprehensive literature review that establishes Australian‐based evidence to support the development, prioritisation and implementation of healthy built environment policies and practices. Another ongoing study examines the design features, social interventions and locational qualities that positively benefit human health. Formal courses, workshops, public lectures and e‐learning develop professional capacity, as well as skills in interdisciplinary practice to support productive collaborations between health professionals and planners. The third area involves working with government and non‐government agencies, and the private sector and the community, to advocate closer links between health and the built environment. Our paper presents an overview of the HBEP's major achievements. We conclude with a critical review of the challenges, revealing lessons in bringing health and planning closer together to create health‐supportive cities for the 21st century. Abstract : Preventing contemporary chronic disease is a complex problem that can only be addressed by collaborative partnerships. The Healthy Built Environments Program is an exemplar of such a partnership. It brings health and the built environment together to create environments that support and encourage people to lead healthy lives on a daily basis.